Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 pada Materi Transformasi Geometri dengan Model Pembelajaran discovery Learning di SMK Bina Nusa Slawi Kabupaten Tegal - Reksaningrum, Mita; Muljani, Sutjie (Universitas Pancasakti Tegal, 2022)
21st century innovative learning is a series of activities undertaken and developed by educators in designing learning to facilitate learners in acquiring knowledge through the achievement of innovative skills of the 21st century. Geometric transformation is one of the subjects in mathematics. Based on the 2013 curriculum, geometric transformation is delivered to students of class XI vocational high school level. In this subject there are many formulas or concepts that require visualization to help learners understand these concepts. This causes learners to have difficulty understanding the material in the subject of geometric transformation. Basically learners learn through something concrete. To understand abstract concepts learners need concrete objects as intermediaries or visualizations. In learning mathematics, the learning experience of learners is very important. For that, a learning innovation is needed that can provide direct experience to students. One such innovation is the use of the Discovery Learning (DL) learning model. In this study discusses the analysis of learning plans, especially discovery learning in geometric transformation materials. In addition, it also discusses the analysis of other Learning Plans included in 21st century learning innovations including learning plans using problem based learning (PBL) and Project Based Learning (PJBL) models. Beerdasarkan the results of analysts to RPP that the three RPPs analyzed have met the characteristics of 21st century learning which includes collaboration with learners, the application of HOTS and integrated with IT.